Freak out! : animals beyond your wildest imagination - Clarke, Ginjer L.; Mueller, Pete (New York : Grosset & Dunlap, 2006)
Simple text and illustrations describe a number of strange creatures including the giant pangolin, narwhale, king vulture, and walking stick.
2.5
K-3
Keywords: Animals -- Miscellanea -- Juvenile literature; Animals -- Miscellanea; Animals -- Miscellanea